Unboundedness of classical global solutions of parabolic equations with forcing terms - Yoshida, Norio (International Journal of Advanced Mathematical Sciences, 2013)
Semilinear parabolic equations with forcing terms are discussed, and sufficient conditions for every classical global solution of boundary value problems to be unbounded on a cylindrical domain in n-dimensional Euclidean space. The approach used is to reduce the multi-dimensional problems to one-dimensional problems for first-order ordinary differential inequalities.